2005
DOI: 10.1152/ajpgi.00206.2004
|View full text |Cite
|
Sign up to set email alerts
|

Luminal bacterial flora determines physiological expression of intestinal epithelial cytoprotective heat shock proteins 25 and 72

Abstract: and 72 are expressed normally by surface colonocytes but not by small intestinal enterocytes. We hypothesized that luminal commensal microflora maintain the observed colonocyte HSP expression. The ability of the small intestine to respond to bacteria and their products and modulate HSPs has not been determined. The effects of luminal bacterial flora in surgically created midjejunal self-filling (SFL) vs. self-emptying (SEL) small-bowel blind loops on epithelial HSP expression were studied. HSP25 and HSP72 expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
100
2
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 112 publications
(109 citation statements)
references
References 58 publications
(64 reference statements)
5
100
2
2
Order By: Relevance
“…Thus, cell protection is possibly enhanced because of chaperone activity, mostly ascribed to HSP70 family members (193) . It was shown that HSP25/27 need SCFA for basal expression in epithelial cells of the colon and in the distal small intestine in vivo in the rat (194,195) , which is in agreement with the results obtained in the calf (8) . In vitro, SCFA enhance the expression of HSP25/27 in a dose-and time-dependent manner, an effect that is transcriptionally regulated (196) , and protect rat intestinal epithelial cells from injury (194) .…”
Section: Mechanisms Of Action Of Butyrate In Physiological and Patholsupporting
confidence: 89%
“…Thus, cell protection is possibly enhanced because of chaperone activity, mostly ascribed to HSP70 family members (193) . It was shown that HSP25/27 need SCFA for basal expression in epithelial cells of the colon and in the distal small intestine in vivo in the rat (194,195) , which is in agreement with the results obtained in the calf (8) . In vitro, SCFA enhance the expression of HSP25/27 in a dose-and time-dependent manner, an effect that is transcriptionally regulated (196) , and protect rat intestinal epithelial cells from injury (194) .…”
Section: Mechanisms Of Action Of Butyrate In Physiological and Patholsupporting
confidence: 89%
“…The distribution of Hsp70 may be related to the protection function of molecular chaperones (Arvans et al 2005;Yu et al 2008). Immunolabeling showed that the Hsp70 protein was predominantly localized in the cytoplasm of epithelial cell.…”
Section: Discussionmentioning
confidence: 99%
“…In small intestine, there is normally very low basal expression of inducible heat shock protein, and blind-loop studies have shown that heat shock protein expression increases in the presence of bacteria (1). When blind loops crafted from small intestine are surgically attached to the colon so that they self-empty with peristalsis into the colon, they do not become colonized with bacteria and heat shock protein expression remains low.…”
Section: Discussionmentioning
confidence: 99%
“…Presence of bacteria appears to upregulate expression of inducible heat shock proteins (1), and both TLR signaling and the induction of heat shock proteins by luminal bacteria are thought to play important roles in intestinal homeostasis (19). There are vast numbers of flagellated bacteria in the normal enteric flora of the intestine, and hence there are large quantities of flagellin circulating in the gut luminal contents, and yet the relative contribution and role of flagellin in intestinal homeostasis remains largely unknown.…”
mentioning
confidence: 99%